Darth Plagueis [compact disc, unabridged] - Luceno, James, 1947- (Random House Audio Publishing, 2011)
A tale of two Siths. At long last, the story of the mysterious Sith Lord, Darth Plagueis, and his apprentice, Darth Sidious, is revealed.